Productivity gains and work conditions in coercive labor markets: Experimental evidence from the Bangladesh brick sector - Grant Miller; Debashish Biswas; Aprajit Mahajan; Kimberly Singer Babiarz; Nina Brooks; Jessie Brunner; Sania Ashraf; Jack Shane; Alvise Scarabosio; Sameer Maithel; Shoeb Ahmed; Moogdho Mahzab; et al. (Proceedings of the National Academy of Sciences, 2026)
Productivity growth in competitive labor markets can improve worker welfare over time through higher wages or better conditions, but it is unclear if productivity gains benefit workers in coercive labor markets (where force or threats shape employment). We examine this issue in the Bangladesh brick sector using a randomized trial that introduced a more efficient production method. Despite large productivity improvements, we find no reduction in (high) rates of labor trafficking or child labor. These findings suggest that in the short-term, productivity growth alone may be insufficient to improve work conditions in coercive settings.